DAMPAK PARTISIPASI ANGGARAN DAN PENEKANAN ANGGARAN TERHADAP SENJANGAN ANGGARAN - Wismarita Wismarita; Elsa Meirina (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The aim of this research is to determine the impact of budget participation and budget emphasis on budget slack. Using purposive sampling technique was applied to determine the sample. The sample in this study were employees of the finance and budget department in Padang City Government agencies who met the criteria. The number of samples used was 145 respondents who were taken based on predetermined criteria. Data was collected using a questionnaire which was measured using a Likert scale. The research results show that budget participation has a positive and significant impact on budgetary slack as indicated by a significant value of 0.000, budget emphasis has a positive and insignificant impact on budgetary slack as indicated by a significant value of 0.299, while budget participation and budget emphasis have a positive impact and simultaneously significant for the budget gap as indicated by a significant value of 0.000